Ordinance no. 260, § 5, Colfax City Council (1902) (Colfax, Washington). - (:unkn) unknown (My University, 1902)
It shall be unlawful for any person within the corporate limits of the city of Colfax to discharge any fire arms, bomb or xxxx cannon fire cracker ,or to shoot any sling shot, or to fl^ourish or exhibit any dangerous weapon in any manner that will cause terror|to the people passing, or exhibit in a rude, angry, or threatening manner in a crowd of two or more persons, any pistol, bowie knife, or other dangerous weapon."
Keywords: BRANDISHING; DISCHARGE